ANALISIS BURDEN OF DISEASE HIPERTENSI PADA MASYARAKAT DI KABUPATEN KEDIRI - Atika Binti Utari; Thinni Nurul Rochmah (Universitas Airlangga, 2019)
The incidence of hypertension is the highest non-communicable disease in Kediri in 2016. The prevalence of hypertension in Kediri reaches 27.9. This situation even exceeds the prevalence rate in East Java (26.2). This study aims to calculate the value of economic losses caused by hypertension sufferers in Kediri. This research is a quantitative research with the cross-sectional method. The primary data collection was done by interviewing 100 hypertension sufferers. The results show that the direct medical cost incurred by patients due to hypertension is IDR 563,360 per capita. Meanwhile, the indirect costs to be incurred by patients during suffering hypertension reach IDR 789,272 per capita. Disability-Adjusted Life Years or years lost due to premature death and disability caused by hypertension disease in Kediri regency amount to 189,915 years. Consequently, the Burden of disease value obtained due to hypertension in Kediri District is IDR 330,882,930,485. It can be concluded that the economic burden caused by hypertension is significantly high. The indirect costs incurred by the patients are greater than the direct costs. Therefore, it is recommended to intensify the dissemination and preventive efforts to decrease the incidence of hypertension.